Author Correction: Non-professional phagocytosis: a general feature of normal tissue cells (Scientific Reports, (2019), 9, 1, (11875), 10.1038/s41598-019-48370-3) - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-06-16